Novel transition metal phosphates (TMPs) - enhanced catalyst for electrochemical water splitting - Afrina Zaidi (Nanyang Technological University, 2022)
As the world moves toward a hydrogen economy and environmental sustainability, an effective and cost-effective electrocatalyst for hydrogen evolution reaction (HER) in electrochemical water splitting becomes increasingly important. We researched and synthesised an optimum metal phosphate with model stoichiometric ratio of Cobalt (Co) and Molybdenum (Mo) components to improve HER performance in this paper. To introduce Mo dopant to our cobalt phosphate (Co2P) synthesis, the ratio of Mo in our synthesis is as follows [Co2P+Mox% ] is varied where x = 5%, 10%, 15%, 20% and 25% . We used X-ray Diffraction (XRD), Field Emission Scanning Electron Microscope (FESEM), X-ray Spectroscopy (XPS), Linear Sweep Voltammetry (LSV), Tafel plot measurements, and durability tests to evaluate the efficacy of Mo doped Co2P as electrocatalyst for HER performance. Based on our findings, Co2P+Mo10% doped is the optimal HER catalyst in terms of its HER activity and durability. Surface changes of Co atoms caused by Mo doping result in Co's presence as a dominating phase, resulting in strong HER activity. This finding suggests that more research is needed to develop a non-noble catalyst for HER